Smoking and symbolism: children, communication and cigarettes. - Rugkåsa, J; Kennedy, O; Barton, M; Abaunza, P; Treacy, M; Knox, B (2001)
Health promotion, with its concern with empowerment and autonomy, must recognize the agency of its target population. Based on 85 in-depth interviews with 10- to 11-year-old children throughout Northern Ireland, this paper argues that it is necessary to focus on the social relations of children if we are to understand and prevent childhood smoking. Addressing the complex issue of childhood agency, it is argued that regardless of various restrictions to their choices, children can act intentionally in constructing their identities. Instead of viewing the smoking children as communicating with the adult world, we focus on smoking as negotiation of status within the children's culture. Such negotiations utilize symbolism derived from and shared with the 'adult world'. It is important that those analyzing children's lives understand children's ideas and behaviour on their own terms. We must make sure that the very concepts in which the children's experiences are put are appropriate ones. It is suggested that the metaphor 'rite of passage' and terminology such as peer 'pressure' versus adult 'influence', commonly used to analyse the children's smoking behaviour, may actually conceal important aspects of childhood agency.